URGENSI PENGGUNAAN SANKSI HUKUM PIDANA DALAM KONTEKS PENANGGULANGAN KEJAHATAN - Pratiwi Ayu Sri Daulat (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2018)
In order to carry out the crime prevention and control policy, there are two ways thatcan be carried out, namely the use of penal facilities or criminal (legal) sanctions,and the use of other facilities (nonpenal). Thus the use of criminal (legal) sanctions isone of the policies in criminal politics, which in this case is not a means that occupiesa strategic position and causes many problems. Moreover, if it is associated with theuse of criminal sanctions to achieve the purpose of prevention as one of the premise ofabolitionist understanding. As a means of law enforcement policy in order to controlcrime, the use of criminal (legal) sanctions is not an absolute. Even if it will be used,then the problem is the policy of its use must be rational by paying attention to thehumanistic approach and social interests that contain certain values that need to beprotected. As a criminal policy, the extreme attitude to eliminate criminal (legal)sanctions is not a policy step. Because what needs to be done in policies to controland overcome crime is an integrated approach between penal and non-formalpolicies. This non-formal activity occupies a key and strategic position that must beintensified and streamlined in controlling and overcoming crime, not eliminatingcriminal law.